Pengaruh Takaran Pupuk Kompos Feses Kuda dan Jarak Tanam terhadap Pertumbuhan dan Hasil Bawang Daun (Allium Fistulosum L.) - Fouk, Yuventus; ceunfin, Syprianus; Gumelar, Asep Ikhsan (Fakultas Pertanian, Sains, dan Kesehatan, Universitas Timor, 2024)
This research aims to determine the effect of the dose of compost mixed with horse feces and plant spacing on the growth and yield of leek plants (Allium fistulosum L.). This research was carried out in October 2022 at the Agrotechnology Study Program Experimental Field and the Laboratory of the Faculty of Agriculture, University of Timor. The design used in this research is a two-factorial split plot design. The first factor is the use of organic fertilizer mixed with horse feces, consisting of 4 levels, namely: without horse compost, 30 t/ha horse compost, 20 t/ha horse compost, and 10 t/ha horse compost. The second factor is the planting distance, which consists of 3 levels: 15 cm x 20 cm, 20 cm x 20 cm, and 25 cm x 20 cm. There were 12 treatment combinations, repeated three times, so there were 36 experimental units. The results of the research showed that there was an interaction between the treatment of giving horse compost fertilizer and the planting distance on the observed parameters of soil moisture content and root volume. The combination treatment of giving a dose of horse feces compost of 30 t/ha and a planting distance of 20 cm x 20 cm resulted in the highest number of leaves. The appropriate dose of horse feces compost for cultivating spring onions is 20 t/ha. This is proven by the highest values obtained for the harvest index parameters: economic weight per plot, economic weight per hectare, temperature, and plant height. This is proven by the highest values obtained for the harvest index parameters, economic weight per plot, economic weight per hectare, temperature, and plant height.